On a New Subspecies of Ussuriana fani Koiwaya (Lepidoptera, Lycaenidae, Theclini) Discovered from northern China - Gu, Yu; Bi, Ming-Lei; Lin, Rung-Juen; Hsu, Yu-Feng (Zootaxa, 2019)
Ussuriana fani wangi, ssp. nov. is described and illustrated from Baihuashan of Taihangshan Mountain Range, Beijing. This new subspecies utilizes Fraxinus bungeana as the larval hostplant, representing the first record of U. fani in northern China. The immature biology, larval morphology, and data of COI barcode all indicate the population belonging to U. fani rather than superficially similar U. michaelis.